Buddha-Nature and Personality as the Ground of Ethics: A Metaethical Dialogue Between Dōgen and Berdyaev - Sevilla, Anton Luis (Archīum Ateneo, 2024)
This paper seeks to contribute to the ongoing Buddhist-Christian dialogue by bringing together the teachings of Zen Master Dōgen and the Russian Christian philosopher Nikolai Berdyaev. This dialogue discusses a metaethical question: What is the foundation of ethical practice? I aim to show that Dōgen’s idea of “buddha-nature” and Berdyaev’s idea of “personality” can be understood as the foundations of ethical practice in ways that are similar and mutually clarifying in their total affirmation of human temporal existence. We begin by discussing the general contours of Dōgen’s practice-realization and Berdyaev’s creative ethics, and then proceed to a comparative examination of the foundation of ethics found in Dōgen’s notion of Buddha-nature and Berdyaev’s notion of personality. The comparison considers four facets of Buddha-nature and personality: being, time, nothingness, and impermanence. First, we show how both thinkers consider the ground of ethics to be something inseparable from the entire being of an individual and the being of all existence as a whole. This refutes the tendency to see the foundation of goodness as a mere fragment of human existence or as restricted to particular existents. second, we show how both thinkers consider this foundation to be manifest not merely in the future or the past, but in every moment seen as a whole in itself. Third, we examine the collision between this immanent foundation and individuality, and show how the non-substantiality of Buddha nature and God make room for creative and individual expressions of authenticity. Finally, we consider the problem of impermanence, and show how the ground of ethics is not an escape from impermanence but an acceptance and embracing of this impermanence as the ground of the efficacy and dynamism of ethical practice.